ZrN tritium-resistant coating and preparation method thereof
Through radio frequency magnetron sputtering technology, the high crystallinity ZrN tritium resist coating was deposited on nuclear structural materials, which solved the corrosion problem of solid tritium proliferator on structural materials, and achieved efficient tritium resisting effect. It was suitable for nuclear fusion reactors. , has excellent corrosion resistance and tritium resistance.
Patent Information
- Application Number
- CN202411343036.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-25
- Publication Date
- 2024-12-27
AI Technical Summary
Solid tritium proliferator has a corrosive and destructive effect on structural materials, affecting the effect of tritium proliferation cladding, and lacks a high crystallinity tritium-retardant coating.
The ZrN tritium-resistance coating was deposited on the substrate of the nuclear structural material by radio frequency magnetron sputtering technology. By adjusting the sputtering parameters such as target distance, vacuum degree, argon and nitrogen flow, a face-centered cubic ZrN film with high crystallinity was obtained. .
It realizes a high crystallinity, density and high purity ZrN tritium-retardant coating, which significantly improves corrosion resistance and tritium-retardant penetration performance. It is suitable for harsh fusion reactor environments, is energy-saving and environmentally friendly, and has a simple preparation process and low cost.
Smart Images

Figure CN119194353A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of coatings, and in particular to a ZrN tritium barrier coating and a preparation method thereof. Background Art
[0002] Contemporary energy is gradually facing difficult challenges such as resource depletion, environmental pollution, and difficulty in meeting human development needs. As an ideal clean energy, controlled thermonuclear fusion energy is regarded as the "ultimate energy" because of its safety, convenient fuel storage, and environmental friendliness.
[0003] The tritium breeder blanket is one of the core components of a nuclear fusion reactor, with functions such as energy extraction and tritium breeding. Solid tritium breeder blanket (HCPB) is the most commercially promising nuclear fusion reactor breeder blanket because it can operate in a high temperature environment and has no magnetohydrodynamic effect. HCPB includes tritium breeder materials (such as Li4SiO4 and Li2TiO3), neutron multipliers (such as Be) and structural materials (such as 316LN austenitic stainless steel, low-activated ferrite martensitic steel). The proliferation of tritium in HCPB depends on the self-sustaining reaction of tritium, but tritium can easily penetrate into structural materials, accelerate the aging process of materials, and even cause the leakage of radioactive tritium, inducing safety accidents. In addition, solid tritium breeders also have a corrosive and destructive effect on structural materials, further affecting the effectiveness of tritium breeder blankets. At present, it is proposed internationally that coating the surface of structural materials with tritium barrier coatings is an effective way to solve this problem.
[0004] As a group IVa transition metal nitride, ZrN has good wear and corrosion resistance, excellent mechanical properties and high radiation resistance; ZrN coating can increase the self-corrosion potential of the substrate, while reducing the corrosion current, significantly improving the corrosion resistance of the substrate. These excellent properties make it widely used in the field of industrial technology, such as as a protective and decorative coating, a diffusion barrier in microelectronic devices, and a corrosion-resistant coating for optical and mechanical parts. However, ZrN lacks the application and research of tritium barrier coating in nuclear fusion and nuclear fission reactors; and for tritium barrier coating, high crystallinity of the coating is a key factor. At present, in conventional fields such as coating and microelectronic devices, the existing ZrN coating preparation process has a low degree of crystallinity and lacks application in tritium barrier. Therefore, it is urgent to establish a preparation method for a high-crystallinity ZrN coating suitable for tritium barrier. Summary of the invention
[0005] The technical problem to be solved by the present invention is that solid tritium breeders have a corrosive and destructive effect on structural materials, which will affect the effectiveness of tritium breeding blankets, and there is a lack of tritium barrier coatings with good tritium barrier effects.
[0006] One of the purposes is to provide a method for preparing a ZrN tritium barrier coating, and to provide a method for preparing a ZrN coating with high crystallinity and good tritium barrier effect for a solid tritium breeding blanket.
[0007] The second purpose is to provide a ZrN coating with high crystallinity and good tritium barrier effect.
[0008] The present invention is achieved through the following technical solutions:
[0009] A method for preparing a ZrN tritium barrier coating comprises the following steps: using Zr as a target material and nitrogen as a reaction gas, and depositing the ZrN tritium barrier coating on the surface of a substrate by magnetron sputtering.
[0010] As a possible design, the above preparation method includes the following steps:
[0011] Fix the substrate on the sputtering table and adjust the distance between the sputtering table and the target;
[0012] Adjust the vacuum degree, introduce argon gas to the starting pressure, and start pre-sputtering after the plasma is started;
[0013] Introduce the reaction gas, adjust the flow rate of argon and reaction gas, and start sputtering after reaching the working pressure;
[0014] After the sputtering is completed and the sputtering table is cooled, the substrate with the ZrN tritium barrier coating sputtered thereon is taken out.
[0015] As a possible design, the substrate may be pre-treated before being fixed on the sputtering table: the substrate may be ground, polished, cleaned and dried.
[0016] As a possible design, the grinding and polishing includes rough grinding, fine grinding, super fine grinding and polishing performed sequentially.
[0017] As a possible design, the substrate is 316LN austenitic stainless steel.
[0018] As a possible design, the target material is a Zr target with a purity of 99.999%.
[0019] As a possible design, the back vacuum degree during the pre-sputtering is 4×10 -5 Pa~6×10 -5 Pa, the purity of the argon gas is 99.999%, the starting gas pressure is 4-6 Pa, the pre-sputtering power is 100-200 W, the working gas pressure is 1-2.5 Pa, and the pre-sputtering time is 5-10 min.
[0020] As a possible design, the purity of the above-mentioned reaction gas is 99.999%, the argon gas flow rate during the formal sputtering is 60-80sccm, the reaction gas flow rate is 1-5sccm, and the formal sputtering power is 100-200W.
[0021] As a possible design, the flow valve angle is also adjusted during the formal sputtering, and the flow valve angle is 40 to 60 degrees.
[0022] The present invention also provides a ZrN tritium barrier coating prepared by the above preparation method.
[0023] Compared with the prior art, the present invention has the following advantages and beneficial effects:
[0024] The invention is based on radio frequency magnetron sputtering technology, and a high-crystallinity ZrN tritium barrier coating is sputtered on a nuclear structural material substrate. The ZrN obtained by the method is face-centered cubic closest packing, and is accompanied by preferential growth with a diffraction angle (111) orientation, and can have more excellent corrosion resistance and tritium penetration resistance performance; and the (111) peak has a very high peak value and a low half-height width, and has good tritium penetration resistance due to high crystallinity; through low nitrogen flow regulation, the obtained film surface is uniform and dense, has a high surface flatness, and is free of defects such as cracks and holes; the film grains have regular shapes, uniform size distribution, and an average grain size of 50 to 61 nm; the elements are evenly distributed, and there are no impurity elements.
[0025] The ZrN tritium barrier coating prepared by the invention has high crystallinity, high density and high purity.
[0026] Compared with the traditional preparation process, the present invention can obtain a ZrN film with high crystallinity at room temperature, thereby requiring less energy in the overall film preparation process, thereby improving energy conservation and environmental protection. At the same time, the high crystallinity ZrN film is expected to have better performance to meet the harsh service environment requirements of the tritium barrier coating of the fusion reactor.
[0027] The preparation process of the invention is simple, low in cost, high in coating efficiency and good in repeatability. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] In order to more clearly illustrate the technical solutions of the exemplary embodiments of the present invention, the following briefly introduces the drawings required for use in the embodiments. It should be understood that the following drawings only illustrate certain embodiments of the present invention and should not be regarded as limiting the scope. For those of ordinary skill in the art, other relevant drawings can be obtained based on these drawings without creative work. In the drawings:
[0029] Figure 1 This is the XRD test diagram of Example 3 of the present invention;
[0030] Figure 2 The SEM surface image and cross-sectional image of Example 3 of the present invention;
[0031] Figure 3 This is a grain size diagram of Example 3 of the present invention;
[0032] Figure 4 The EDS element distribution diagram and content test diagram of Example 3 of the present invention;
[0033] Figure 5 This is the XRD test diagram of Comparative Example 1 of the present invention;
[0034] Figure 6 This is the XRD test diagram of Comparative Example 2 of the present invention;
[0035] Figure 7 This is the XRD test diagram of Comparative Example 3 of the present invention. DETAILED DESCRIPTION
[0036] In order to make the objectives, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with embodiments and drawings. The exemplary embodiments of the present invention and their description are only used to explain the present invention and are not intended to limit the present invention.
[0037] In the prior art, solid tritium breeders have a corrosive and destructive effect on structural materials, which will affect the efficacy of tritium breeding blankets, and there is a lack of tritium barrier coatings with good tritium barrier effects. The present invention provides a method for preparing a ZrN tritium barrier coating, and the prepared ZrN coating has high crystallinity, good hydrogen barrier effect, and resistance to lithium ceramic corrosion, which fills the gap in related research in the field.
[0038] A method for preparing a ZrN tritium barrier coating comprises the following steps: using Zr as a target material and nitrogen as a reaction gas, and depositing the ZrN tritium barrier coating on the surface of a substrate by magnetron sputtering.
[0039] In some embodiments of the present invention, the above preparation method comprises the following steps:
[0040] S1. Fix the substrate on the sputtering table and adjust the distance between the sputtering table and the target.
[0041] The present invention adjusts the distance between the sputtering table and the target material so that particles sputtered from the target material can be quickly deposited on the substrate, thereby reducing energy loss, improving deposition efficiency, and improving the uniformity of the coating deposited on the surface of the substrate and improving the quality of the thin film. In addition, at this distance, mutual interference between the target material and the substrate can be avoided, thereby improving film formation efficiency.
[0042] Preferably, the distance between the sputtering table and the target is 4 to 8 cm, so that the distance between the substrate and the target is 4 to 8 cm. More preferably, the distance can be 5 cm, 6 cm, 7 cm or other values.
[0043] In some embodiments of the present invention, the substrate is 316LN austenitic stainless steel.
[0044] Preferably, the substrate has a diameter of 12 mm and a thickness of 0.5 mm.
[0045] In some embodiments of the present invention, the target material is a Zr target with a purity of 99.999%.
[0046] Preferably, before the substrate is fixed on the sputtering table, the sputtering chamber is cleaned to remove impurities and contaminants.
[0047] S2. Adjust the vacuum degree, introduce argon gas to the starting pressure, and start pre-sputtering after the plasma is started.
[0048] Through pre-sputtering, impurities and oxide layers on the surface of the target material are removed, so that the coating deposited on the surface of the substrate has high purity during the subsequent formal sputtering.
[0049] In some embodiments of the present invention, the back vacuum degree during the pre-sputtering is 4×10 -5 Pa~6×10 -5 Pa, the purity of argon is 99.999%, the starting pressure is 4-6 Pa, the pre-sputtering power is 100-200 W, the working pressure is 1-2.5 Pa, and the pre-sputtering time is 5-10 min. The back vacuum is preferably 5×10 -5 Pa, the starting gas pressure is preferably 5 Pa, the working gas pressure is preferably 1.5 Pa, 2 Pa or other values, and the pre-sputtering time is preferably 6 min, 7 min, 8 min or other values.
[0050] After research, the inventors found that pre-sputtering can remove pollutants on the surface of the target material and play a certain cleaning effect. The film after pre-sputtering has higher purity and better bonding strength. When the vacuum degree is within this range, the impurity content of the film is lower and the sputtering efficiency is high.
[0051] Preferably, the back vacuum degree can be 4.5×10 -5 Pa, 5×10 -5 Pa, 5.5×10 -5 Pa or other values.
[0052] Preferably, before pre-sputtering, the mechanical pump and the molecular pump are turned on at once, and after the vacuum degree reaches the experimental conditions, argon gas is introduced to the starting pressure, and the cooling water system and the radio frequency power supply are turned on to perform pre-sputtering.
[0053] S3. Introduce reaction gas, adjust the flow rate of argon and reaction gas, and start sputtering after reaching the working pressure.
[0054] In some embodiments of the present invention, the purity of the reaction gas is 99.999%, the argon flow rate during the formal sputtering is 60-80 sccm, the reaction gas flow rate is 1-5 sccm, and the formal sputtering power is 100-200 W. The argon flow rate can be 65 sccm, 70 sccm, 75 sccm or other flow rates; the reaction gas flow rate can be 2 sccm, 3 sccm, 4 sccm or other values; the formal sputtering power can be 120 W, 160 W, 140 W, 180 W or other values.
[0055] After research, the inventors found that when the reaction gas flow rate is 1 to 5 sccm, the film obtained at this flow rate has the highest crystallinity and high film forming efficiency; when the flow rate is higher than 5 sccm, an amorphous coating with poor tritium permeability resistance will be obtained, and the coating has poor bonding strength and is easily oxidized.
[0056] In some embodiments of the present invention, the flow valve angle is also adjusted during the formal sputtering, and the flow valve angle is 40-60°. The flow valve angle can be 45°, 50°, 55° or other values.
[0057] When the flow valve is at this angle, it can ensure that the film is prepared under a good vacuum degree while ensuring the coating efficiency and film quality.
[0058] Preferably, the working gas pressure during the sputtering is 1-2.5 Pa, and may be 1.5 Pa, 1.3 Pa, 1.8 Pa, 2 Pa or other values.
[0059] S4. After the sputtering is completed and the sputtering table is cooled, the substrate with the ZrN tritium barrier coating sputtered thereon is taken out.
[0060] In some embodiments of the present invention, before the substrate is fixed on the sputtering table, the process further includes S0, pretreatment: grinding and polishing the substrate, cleaning and drying the substrate.
[0061] By pre-treating the substrate surface, impurities and oxides on the substrate surface can be removed, so that the subsequent sputtered coating has a high degree of bonding with the substrate.
[0062] Preferably, the pretreatment is to grind and polish the substrate with metallographic sandpaper, ultrasonically clean it with anhydrous ethanol, and blow dry it for standby use.
[0063] Choosing metallographic sandpaper for grinding can improve the uniformity of grinding and the grinding efficiency, and it can be cleaned with anhydrous ethanol after grinding. Since there may be some organic matter and oxide layer on the surface of the substrate after grinding, anhydrous ethanol has a good cleaning effect on them.
[0064] In some embodiments of the present invention, the grinding and polishing includes sequentially performing rough grinding, fine grinding, super fine grinding and polishing.
[0065] By performing the above grinding in sequence, the uniformity of the film thickness can be improved. If the grinding and polishing is not sufficient, the uniformity of the film thickness will be poor, which will affect the hydrogen penetration resistance effect.
[0066] Preferably, the rough grinding is performed with SiC sandpaper of 400-800 meshes until there is no pollutant such as oxide, rust and residual paint on the surface of the substrate; it can be 400 mesh, 500 mesh, 600 mesh, 700 mesh, 800 mesh or other meshes.
[0067] The fine grinding is specifically carried out with SiC sandpaper of 1000-2000 meshes, until the substrate surface is free of heavy rust, stains, grooves, scratches and flaws, etc.; it can be 1100 mesh, 1200 mesh, 1300 mesh, 1400 mesh, 1800 mesh, 1900 mesh or other meshes.
[0068] The ultra-fine grinding is specifically carried out with 3000 mesh SiC sandpaper, until the substrate surface is free of defects, rust and processing marks, and the surface achieves a mist effect. SiC sandpaper has high hardness and wear resistance, which can ensure the grinding effect of the stainless steel surface;
[0069] The polishing is specifically performed using a polishing cloth until the surface of the substrate reaches a mirror effect, which can clearly reflect the image of the object.
[0070] The present invention also provides a ZrN tritium barrier coating prepared by the above preparation method.
[0071] Example 1
[0072] A method for preparing a ZrN tritium barrier coating, the specific steps of which are as follows:
[0073] S0: Use metallographic sandpaper (SiC) to grind the 316LN austenitic stainless steel substrate with a diameter of 12 mm and a thickness of 0.5 mm in sequence, through coarse grinding, fine grinding, super fine grinding and polishing, and finally achieve a mirror effect, which can clearly reflect the image of the object, and then put it into an ultrasonic cleaning machine, use anhydrous ethanol to ultrasonically clean it for 15 minutes, and blow it dry for use;
[0074] S1: After cleaning the sputtering chamber, fix the 316LN substrate on the sputtering table with conductive glue, and adjust the distance between the sputtering table and the Zr target with a purity of 99.999% to 4 cm;
[0075] S2: Turn on the mechanical pump and molecular pump in sequence, and wait until the vacuum reaches 4×10 -4 After the plasma reaches 6 Pa, argon gas with a purity of 99.999% is introduced to 6Pa, the cooling water system and the radio frequency power supply are turned on, and after the plasma is ignited, the radio frequency power supply power is set to 100W, and the argon gas and flow valve are adjusted to make the pre-sputtering working pressure to 2.5Pa. Pre-sputter for 10 minutes to remove residual impurities and oxide layers on the surface of the target;
[0076] S3: introduce nitrogen gas with a purity of 99.999% as the reaction gas, adjust the argon gas to 79 sccm, the nitrogen flow rate to 5 sccm, adjust the flow valve angle to 53°, set the RF power to 100 W when the formal sputtering working pressure is 1.3 Pa, and formally sputter for 30 minutes;
[0077] S4: After the sputtering is completed, wait for the sputtering table to cool down to room temperature, take out the ZrN thin film sample, and end the preparation.
[0078] The phase structure of the ZrN coating in this embodiment is a high-crystallinity ZrN with a (111) peak preferred orientation. The film surface is uniform and dense, has a high surface flatness, is free of defects such as cracks and holes, and has a high sputtering rate during the preparation process. The prepared film has regular grain shape, uniform size distribution, and clear grain boundaries. The film elements are evenly distributed and meet the ZrN stoichiometric ratio. All of this information shows that the present invention prepares a high-crystallinity, high-density and high-quality ZrN tritium barrier coating.
[0079] Example 2
[0080] A method for preparing a ZrN tritium barrier coating, the specific steps of which are as follows:
[0081] S0: Use metallographic sandpaper (SiC) to grind the 316LN austenitic stainless steel substrate with a diameter of 12 mm and a thickness of 0.5 mm in sequence, through coarse grinding, fine grinding, super fine grinding and polishing, and finally achieve a mirror effect, which can clearly reflect the image of the object, and then put it into an ultrasonic cleaning machine, use anhydrous ethanol to ultrasonically clean it for 15 minutes, and blow it dry for use;
[0082] S1: Clean the sputtering chamber to remove impurities and contaminants, fix the 316LN substrate on the sputtering table with conductive glue, and adjust the distance between the sputtering table and the Zr target with a purity of 99.99% to 8 cm;
[0083] S2: Turn on the mechanical pump and molecular pump in sequence, and wait until the vacuum reaches 6×10 -5 After the plasma is ignited, argon gas with a purity of 99.999% is introduced to 4Pa, the cooling water system and the radio frequency power supply are turned on, and after the plasma is ignited, the radio frequency power supply power is set to 150W, and the argon gas and flow valve are adjusted to make the pre-sputtering working pressure to 2Pa. Pre-sputter for 10 minutes to remove residual impurities and oxide layers on the surface of the target;
[0084] S3: introduce nitrogen gas with a purity of 99.999% as the reaction gas, adjust the argon gas to 78 sccm, the nitrogen flow rate to 6 sccm, adjust the flow valve angle to 50°, set the RF power to 200 W when the formal sputtering working pressure is 1.3 Pa, and formally sputter for 30 minutes;
[0085] S4: After the sputtering is completed, wait for the sputtering table to cool down to room temperature, take out the ZrN thin film sample, and end the preparation.
[0086] The phase structure of the ZrN ceramic film of this embodiment is a high-crystallinity ZrN with a (111) peak preferential orientation. The film surface is uniform and dense, has a high surface flatness, is free of defects such as cracks and holes, and has a high sputtering rate during the preparation process. The prepared film has regular grain shape, uniform size distribution, and clear grain boundaries. The film elements are evenly distributed, basically satisfying the ZrN stoichiometric ratio. All of this information shows that the present invention prepares a new type of tritium barrier coating of ZrN ceramics with high crystallinity, high density and high quality.
[0087] Example 3
[0088] A method for preparing a novel tritium-barrier coating of ZrN ceramics, the specific steps of which are as follows:
[0089] S0: Use metallographic sandpaper (SiC) to grind the 316LN austenitic stainless steel substrate with a diameter of 12 mm and a thickness of 0.5 mm in sequence, through coarse grinding, fine grinding, super fine grinding and polishing, and finally achieve a mirror effect, which can clearly reflect the image of the object, and then put it into an ultrasonic cleaning machine, use anhydrous ethanol to ultrasonically clean it for 15 minutes, and blow it dry for use;
[0090] S1: Clean the sputtering chamber to remove impurities and contaminants, stick the 316LN substrate steadily on the sputtering table with conductive glue, and adjust the distance between the sputtering table and the Zr target with a purity of 99.99% to 6 cm;
[0091] S2: Turn on the mechanical pump and molecular pump in sequence, and wait until the vacuum reaches 5×10 -4 After the plasma reaches 6 Pa, argon gas with a purity of 99.999% is introduced to 6Pa, the cooling water system and the radio frequency power supply are turned on, and after the plasma is ignited, the radio frequency power supply power is set to 200W, and the argon gas and flow valve are adjusted to make the pre-sputtering working pressure to 1.5Pa. Pre-sputter for 10 minutes to remove residual impurities and oxide layers on the surface of the target;
[0092] S3: introduce nitrogen gas with a purity of 99.999%, adjust the argon gas to 80 sccm, the nitrogen flow rate to 5 sccm, adjust the flow valve angle to 55°, set the RF power to 100 W when the formal sputtering working pressure is 1.3 Pa, and formally sputter for 30 minutes;
[0093] S4: After the sputtering is completed, wait for the sputtering table to cool down to room temperature, take out the ZrN thin film sample, and end the preparation.
[0094] The samples were subjected to XRD test, and the results were as follows Figure 1As shown. From the figure, we can observe the diffraction peaks of ZrN and 316LN matrix. The prepared ZrN sample has the most densely packed face-centered cubic structure and is accompanied by (111) orientation preferential growth. At this time, the (111) peak has an extremely high peak value and a small half-height width. These data all indicate that the crystallinity of the film is very excellent.
[0095] The samples were observed by scanning electron microscopy. Figure 2 As shown. The film surface is uniform and dense, with high surface flatness, no defects such as cracks and holes, and no obvious impurity particles. The cross-sectional view shows that the film thickness is 775nm, with a high sputtering rate of 25.83nm / min, no layered columnar structure, and the film shows good density, high crystallinity and high density, which proves its excellent quality and can bring better film performance.
[0096] The sample was observed by scanning electron microscopy, and the microscopic grain morphology of the film can be seen Figure 3 (Left), the grain size statistics can be seen Figure 3 (Right) It can be seen from the figure that the film grains have regular shapes, uniform sizes, and clearly visible grain boundaries. The average grain size is 60.28nm.
[0097] The samples were observed by energy dispersive X-ray spectrometer. Figure 4 shown. Figure 4 The two figures above are element distribution diagrams on the film surface, and the figure below is a statistical diagram of element content. It can be observed that the elements in the film are evenly distributed, and the elements basically meet the ZrN stoichiometric ratio.
[0098] The phase structure of the ZrN ceramic film of this embodiment is a high-crystallinity ZrN with a (111) peak preferential orientation. The film surface is uniform and dense, has a high surface flatness, is free of defects such as cracks and holes, and has a high sputtering rate during the preparation process. The prepared film has regular grain shape, uniform size distribution, and clear grain boundaries. The film elements are evenly distributed, basically satisfying the ZrN stoichiometric ratio. All of this information shows that the present invention prepares a new type of tritium barrier coating of ZrN ceramics with high crystallinity, high density and high quality.
[0099] Comparative Example 1
[0100] This embodiment is basically the same as embodiment 3, except that the pre-sputtering vacuum degree in S2 is 8×10 -5 Pa.
[0101] The samples were subjected to XRD test, and the results were as follows Figure 5 The green line in the figure is the result of Example 3, and the red line is the result of Comparative Example 1. By comparison, it can be seen that the crystallinity of the ZrN phase in Comparative Example 1 is not high, which may be due to the poor vacuum degree of the background.
[0102] Comparative Example 2
[0103] This embodiment is basically the same as Embodiment 3, except that the reaction gas flow rate in S3 is 8 sccm.
[0104] The samples were subjected to XRD test, and the results were as follows Figure 6 The green line in the figure is the result of Example 3, and the red line is the result of Comparative Example 2. By comparison, it can be seen that Comparative Example 2 has no peak at (111), and the crystallinity of the ZrN phase is not high, which may be due to a slight increase in gas flow rate.
[0105] Comparative Example 3
[0106] This embodiment is basically the same as Embodiment 3, except that the angle of the flow valve in S3 is 30°.
[0107] The samples were subjected to XRD test, and the results were as follows Figure 7 The green line in the figure is the result of Example 3, and the red line is the result of Comparative Example 3. By comparison, it can be seen that there is no peak at (111) in Comparative Example 3. The inventors analyzed that this may be because a smaller flow valve angle increases the sputtering pressure, weakens the fluidity of nitrogen, and greatly reduces the crystallinity of the ZrN phase.
[0108] The present invention provides a ZrN tritium barrier coating, which can be used to prepare a fusion reactor tritium barrier coating, promote the frontier development in the field of nuclear fusion energy, and fill the gap in related research in the field.
[0109] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A method for preparing a ZrN tritium barrier coating, characterized in that: With Zr as the target and nitrogen as the reaction gas, the substrate is subjected to magnetron sputtering to deposit a ZrN tritium barrier coating on the surface of the substrate.
2. The method for preparing a ZrN tritium barrier coating according to claim 1, characterized in that: The steps include: Fix the substrate on the sputtering table and adjust the distance between the sputtering table and the target; Adjust the vacuum degree, introduce argon gas to the starting pressure, and start pre-sputtering after the plasma is started; Introduce the reaction gas, adjust the flow rate of argon and reaction gas, and start sputtering after reaching the working pressure; After the sputtering is completed and the sputtering table is cooled, the substrate with the ZrN tritium barrier coating sputtered thereon is taken out.
3. The method for preparing a ZrN tritium barrier coating according to claim 2, characterized in that: The substrate is also pre-treated before being fixed on the sputtering table: the substrate is ground and polished, cleaned and dried; The pretreatment specifically includes grinding and polishing the substrate with metallographic sandpaper, ultrasonically cleaning with anhydrous ethanol, and drying for later use.
4. A method for preparing a ZrN tritium barrier coating according to claim 2 or 3, characterized in that: The grinding and polishing includes rough grinding, fine grinding, super fine grinding and polishing performed in sequence. The rough grinding is specifically performed using 400-800 mesh SiC sandpaper until there is no pollutant such as oxide, rust and residual paint on the surface of the substrate; The fine grinding is specifically performed using SiC sandpaper with a mesh of 1000 to 2000, until the surface of the substrate is free of heavy rust, stains, grooves, scratches and flaws; the ultra-fine grinding is specifically performed using SiC sandpaper with a mesh of 3000, until the surface of the substrate is free of defects, rust and processing marks, and the surface achieves a mist effect; the polishing is specifically performed using a polishing cloth, until the surface of the substrate achieves a mirror effect, which can clearly reflect the image of the object.
5. The method for preparing a ZrN tritium barrier coating according to claim 2, characterized in that: The substrate is 316LN austenitic stainless steel.
6. The method for preparing a ZrN tritium barrier coating according to claim 2, characterized in that: The target material is a Zr target with a purity of 99.999%; Before the substrate is fixed on the sputtering table, the sputtering chamber is cleaned to remove impurities and contaminants.
7. The method for preparing a ZrN tritium barrier coating according to claim 2, characterized in that: The back vacuum degree during the pre-sputtering is 5×10 -5Pa , the purity of the argon gas is 99.999%, the starting gas pressure is 4-6 Pa, the pre-sputtering power is 100-200 W, the working gas pressure is 1-2.5 Pa, and the pre-sputtering time is 5-10 min; Before the pre-sputtering, the mechanical pump and the molecular pump are turned on at once, and after the vacuum degree reaches the experimental condition, argon gas is introduced to the starting pressure, and the cooling water system and the radio frequency power supply are turned on to perform pre-sputtering.
8. The method for preparing a ZrN tritium barrier coating according to claim 2, characterized in that: The purity of the reaction gas is 99.999%, the flow rate of argon gas during the formal sputtering is 60-80 sccm, the flow rate of the reaction gas is 1-5 sccm, and the formal sputtering power is 100-200W.
9. A method for preparing a ZrN tritium barrier coating according to claim 2 or 8, characterized in that: During the formal sputtering, the flow valve angle is also adjusted, and the flow valve angle is 40-60 degrees.
10. A ZrN tritium barrier coating prepared by the preparation method as claimed in any one of claims 1 to 9.
